SISTEM INFORMASI PENDAFTARAN ORGANISASI MASYARAKAT PADA KESBANGPOL DAN HUMAS PROVINSI ACEH - Yusni, M. Rizal; Ahmad, Lukman; Ismail (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
Based on data available at Kesbangpol and Public Relations of Aceh Province, the number of Community Organizations in Aceh Province are mostly Community Organizations that have obtained a Certificate of Registration (SKT) issued by the Unity and Political Office and the rest have not met the requirements to become community organizations as stipulated in the provisions of the Law. Law Number 17 of 2013 concerning Community Organizations. The research objectives were to find out the Information System for Registration of Community Organizations at the Kesbangpol and Public Relations of Aceh Province and to design a Web-based Information System for Registration of Community Organizations at Kesbangpol and Public Relations of Aceh Province. The author collects data with several data collection methods, including the following; Field Studies and Literature Studies with the waterfall method as the method used for system development. Based on the results of observations and the authors can draw a conclusion, among others, this information system for registration of community organizations can make it easy for Kesbangpol and Public Relations of Aceh Province to monitor data and community organizations.